THE NECESSARY EVOLUTION OF COUNTER-INTELLIGENCE IN RESPONSE TO FOREIGN INTERFERENCE - CSIS Executive (The Journal of Intelligence, Conflict and Warfare)
On November 21, 2024, a Canadian Security Intelligence Service (CSIS) Executive presented The Necessary Evolution of Counter Intelligence in response to Foreign Interference for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key theme discussed was how intelligence work has transformed since the end of the Cold War and in response to the threat of Foreign Interference in particular. The presenter outlined why Canada is an attractive target for Foreign Interference threat actors and highlighted how Canada’s intelligence professionals and legislative framework has had to evolve as a result.